Intermittency : the concept of historical reason in recent French philosophy - Gibson, Andrew, 1949- (Edinburgh University Press, 2012)
Explores the concept of historical intermittency in 5 recent French philosophers stoking the embers of French Hegelianism, this book looks at five recent and contemporary French philosophers: Badiou, Jambet, Lardreau, Françoise Proust and Rancière. Each produces a post-Hegelian philosophy of history founded on an assertion of the intermittency of historical value.* a sustained reflection on the character of a contemporary philosophy of history* a new and timely theory of modernity, modern literature and art.